Primary structure of corticotropin-releasing factor from ovine hypothalamus. - Spiess, J (1981)
Sequence analysis was performed of an ovine hypothalamic 41-residue polypeptide that had been postulated to be a putative corticotropin-releasing factor (CRF) because of its high intrinsic corticotropin releasing activity. The NH2-terminal 39 residues of CRF were determined by Edman degradation of 0.6-3.5 nmol of peptide in a Wittmann-Liebold modified Beckman 890C spinning cup sequencer with reverse-phase high-pressure liquid chromatography for the identification of amino acid phenylthiohydantoins (direct micro-sequence analysis). Evidence for residue 40 (isoleucine) was provided by direct micro-sequence analysis of 2.0 nmol of acetylated CRF selectively cleaved at its arginine residues by trypsin prior to analysis. The thermolytic COOH-terminal fragment isoleucyl-alanineamide was characterized as its dansyl derivative. Based on the analytical data, the following primary structure is proposed for ovine hypothalamic CRF: H-Ser-Gln-Glu-Pro-Pro-Ile-Ser-Leu-Asp-Leu-Thr-Phe-His-Leu-Leu-Arg-Glu-Val-Leu-Glu-Met-Thr-Lys-Ala-Asp-Gln-Leu-Ala-Gln-Gln-Ala-His-Ser-Asn-Arg-Lys-Leu-Leu-Asp -Ile-Ala-NH2. In agreement with this proposal, the synthetic replicate of CRF is highly potent in stimulating secretion of both corticotropin and beta-endorphin-like immunoactivities.